Ceph cookbook : practical recipes to design, implement, operate, and manage Ceph storage systems - Umrao, Vikhyat; Singh, Karan; Hackett, Michael (Packt Publishing, 2017)
Over 100 effective recipes to help you design, implement, and troubleshoot manage the software-defined and massively scalable Ceph storage system. About This Book Implement a Ceph cluster successfully and learn to manage it. Recipe based approach in learning the most efficient software defined storage system Implement best practices on improving efficiency and security of your storage cluster Learn to troubleshoot common issues experienced in a Ceph cluster Who This Book Is For This book is targeted at storage and cloud engineers, system administrators, or anyone who is interested in building software defined storage, to power your cloud or virtual infrastructure. If you have basic knowledge of GNU/Linux and storage systems, with no experience of software defined storage solutions and Ceph, but eager to learn then this book is for you What You Will Learn Understand, install, configure, and manage the Ceph storage system Get to grips with performance tuning and benchmarking, and learn practical tips to help run Ceph in production Integrate Ceph with OpenStack Cinder, Glance, and Nova components Deep dive into Ceph object storage, including S3, Swift, and Keystone integration Configure a disaster recovery solution with a Ceph Multi-Site V2 gateway setup and RADOS Block Device mirroring Gain hands-on experience with Ceph Metrics and VSM for cluster monitoring Familiarize yourself with Ceph operations such as maintenance, monitoring, and troubleshooting Understand advanced topics including erasure-coding, CRUSH map, cache pool, and general Ceph cluster maintenance In Detail Ceph is a unified distributed storage system designed for reliability and scalability. This technology has been transforming the software-defined storage industry and is evolving rapidly as a leader with its wide range of support for popular cloud platforms such as OpenStack, and CloudStack, and also for virtualized platforms. Ceph is backed by Red Hat and has been developed by community of developers which has gained immense traction in recent years. This book will guide you right from the basics of Ceph, such as creating blocks, object storage, and filesystem access, to advanced concepts such as cloud integration solutions. The book will also cover practical and easy to implement recipes on CephFS, RGW, and RBD with respect to the major stable release of Ceph Jewel. Towards the end of the book, recipes based on troubleshooting and best practices will help you get to grips wi ...